Can Rights Cure? - Marius Pieterse (Pretoria University Law Press (PULP), 2014)
Can Rights Cure? by Marius Pieterse 2014 ISBN: 978-1-920538-27-9 Pages: 194 Print version: Available Electronic version: Free PDF available